1988
DOI: 10.1111/j.1365-2427.1988.tb00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus transformations in the epilimnion of humic lakes: abiotic interactions between dissolved humic materials and phosphate

Abstract: SUMMARY. 1. Sephadex gel filtration of filtered water from small, Finnish forest lakes demonstrated abiotic movement of 33P from added PO4 to two higher molecular weight fractions. This movement was most pronounced in waters with high humic content which also had high iron content. The two fractions which took up 13P had nominal molecular weights of > 100,000 and 10,000‐20,000. 2. An equilibrium existed between free PO4 and the two fractions. However, one fraction, at least, appeared to exist in two phases, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 31 publications
3
52
0
Order By: Relevance
“…The inhibition might have been partly due to the scavenging of hydroxyl radicals by HA (Christoforidis et al, 2015). In fact, the interactions between iron, phosphorus, light, and organic matter are very complex (Jones et al, 1998;De Haan et al, 1990). The glyphosate is one kind of stable organic phosphorus and the transformation of glyphosate to phosphate by Fe 3þ was inhibited by HA.…”
Section: Effect Of Humic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition might have been partly due to the scavenging of hydroxyl radicals by HA (Christoforidis et al, 2015). In fact, the interactions between iron, phosphorus, light, and organic matter are very complex (Jones et al, 1998;De Haan et al, 1990). The glyphosate is one kind of stable organic phosphorus and the transformation of glyphosate to phosphate by Fe 3þ was inhibited by HA.…”
Section: Effect Of Humic Acidmentioning
confidence: 99%
“…A large quantity of phosphate would be fixed by Fe(III) by forming Fe(OOH)-P complexes or precipitates (Kleeberg et al, 2013), which inhibit the release of phosphorus. Meanwhile, the dissolved phosphate could be released from the phosphorus e humus -iron complex under UV irradiation (Francko andHeath, 1979, 1982;Jones et al, 1998;De Haan et al, 1990). The mechanisms were mainly concluded as following: (1) UV light can damage the phenol group of dissolved humus, which reduced affinity for dissolved iron, thereby promoting dissociation of phosphate; (2) Fe 3 þ of phosphorus e humus -iron complexes can obtain electronic from the dissolution of humus or other sources under UV light, resulting in the release of phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…Koenings & Hooper 1976;Franco & Heath 1982;Jones et al 1988;Wojciechowski 1990;Wojciechowski & Górniak 1990). It is believed that the process of photodegradation of the chelation connectionsof humic acids and minerals compounds, observable in hardwater basins, is one of the factors influencing their eutrophication (Jones et al 1988;Wojciechowski 1990;Wetzel 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Using harsher techniques, Bradford and Peters (1 987) measured an increase in soluble reactive phosphorus after irradiation in 95% of samples from both lakes and rivers. Jones et al (1988) found that exposure to sunlight of the high molecular weight P in water from small Finnish lakes caused a small release of o-P. On the other hand, a partial characterization of the dissolved P pools in the oligotrophic subtropical North Pacific Ocean was reported. The total dissolved phosphorus (TDP) in seawater could be reproducibly subdivided into three chemically distinct pools: soluble reactive phosphorus (SRP, presumably dominated by o-P), UV-labile phosphorus (Puv-L; containing primarily monophosphate esters), and UV-stable phosphorus (Puv.s, containing primarily nucleotide di-and triphosphates, nucleic acids, and other compounds that are resistant to the UV treatment).…”
Section: Introductionmentioning
confidence: 99%